2018
DOI: 10.3390/ijms19030912
|View full text |Cite
|
Sign up to set email alerts
|

Suppression Effect of Astaxanthin on Osteoclast Formation In Vitro and Bone Loss In Vivo

Abstract: Abstract:Osteoporosis is characterized by a reduction of the bone mineral density (BMD) and microarchitectural deterioration of the bone, which lead to bone fragility and susceptibility to fracture. Astaxanthin (AST) has a variety of biological activities, such as a protective effect against asthma or neuroinflammation, antioxidant effect, and decrease of the osteoclast number in the right mandibles in the periodontitis model. Although treatment with AST is known to have an effect on inflammation, no studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 57 publications
4
34
0
Order By: Relevance
“…Osteoporosis, a pandemic health issue affecting generally postmenopausal women, is a systemic skeletal disease known with decreased bone mineral density (BMD) and micro-architectural impairment of the quality of bone tissue [ 1 ]. This debilitating condition of osteoporosis leads to a higher risk of bone brittleness and vulnerability to fracture and is associated with morbidity, mortality, and a reduction in quality of life [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis, a pandemic health issue affecting generally postmenopausal women, is a systemic skeletal disease known with decreased bone mineral density (BMD) and micro-architectural impairment of the quality of bone tissue [ 1 ]. This debilitating condition of osteoporosis leads to a higher risk of bone brittleness and vulnerability to fracture and is associated with morbidity, mortality, and a reduction in quality of life [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analyses were conducted as previously described [ 59 ]. Briefly, the morphometric parameters of the bones (femur and tibia) were determined using a micro-computed tomography (micro-CT) system (Skyscan 1272, Bruker micro-CT, Kontich, Belgium).…”
Section: Methodsmentioning
confidence: 99%
“…The bone and uterus staining were performed as previously described [ 59 , 60 ]. Briefly, the bone samples were fixed in 4% formaldehyde at room temperature, and decalcified in 10% ethylenediaminetetraacetic acid (EDTA).…”
Section: Methodsmentioning
confidence: 99%
“…Astaxanthin has a variety of biological activities such as antioxidant effects or inhibitory effects against asthma or neuro-inflammation [48]. Recently, Hwang demonstrated that anti-osteoporotic effects of astaxanthin on the bone mass of ovariectomized (OVX) mice [48].…”
Section: Astaxanthinmentioning
confidence: 99%
“…Astaxanthin has a variety of biological activities such as antioxidant effects or inhibitory effects against asthma or neuro-inflammation [48]. Recently, Hwang demonstrated that anti-osteoporotic effects of astaxanthin on the bone mass of ovariectomized (OVX) mice [48]. Interestingly, administration of astaxanthin suppressed significantly the increase of serum calcium levels, alkaline phosphatase and tartrate-resistant acid phosphatase (TRAP) activity in the OVX mice.…”
Section: Astaxanthinmentioning
confidence: 99%